Comprehensive Study of Mass Poisoning MBG Program (Legal, Health, Human Rights, Social Perspectives) - Aprilliany Zahra Nur Azzalia Jacob; Rabith Madah Khulaili Harsya; Dian Rositasari; Ainurrafiqa Pelupessy; Muhammad Fachrur Razy Mahka (Yayasan Inovasi Kemajuan Intelektual, 2025)
The Free Nutritious Meals (MBG) program is a strategic government policy to improve the quality of human resources, but its implementation faces serious technical risks in including mass poisoning incidents. This study aims to comprehensively analyze the phenomenon of mass poisoning in the MBG program through four main perspectives: law, health, human rights (HAM), and social. Using a normative-empirical research method with a case study approach, this study explores systemic failures in the food supply chain. The results of the study indicate that mass poisoning is not merely a medical problem, but rather a representation of weak enforcement of food safety regulations, violations of the basic right to safe food, and triggers social distrust in state institutions. This study recommends strengthening food safety protocols, standardizing food supply units, and establishing clear legal accountability mechanisms to protect citizens as rights holders.